Changes of the coronal lumbar-pelvic-femoral alignment after conversion total hip arthroplasty in patients with unilateral ankylosed hip - Takaomi Kobayashi; Tadatsugu Morimoto; Hirohito Hirata; Tomohito Yoshihara; Masatsugu Tsukamoto; Motoki Sonohata; Masaaki Mawatari (Scientific Reports, 2023)
Abstract To elucidate the changes in coronal lumbar-pelvic-femoral alignment after conversion total hip arthroplasty (THA) in patients with unilateral ankylosed hip. A retrospective radiologic study of 48 patients (48 hips) with unilateral hip arthrodesis who underwent conversion THA was conducted. Cobb’s angle of lumbar scoliosis (LS), the pelvic obliquity (PO) angle, and the hip adduction angle (HAA) on standing anterior–posterior spine-pelvis-hip radiographs were measured before and after THA. The differences of LS, PO, and HAA before and after THA were defined as ΔLS, ΔPO, and ΔHAA, respectively. A paired samples t-test or the Wilcoxon signed-rank test were used to compare the absolute values of the LS, PO, and HAA between preoperative and postoperative groups. The Pearson’s correlation coefficient (r) or Spearman’s correlation coefficient (ρ) was calculated to assess the relationship between ΔLS, ΔPO, and ΔHAA and possible associated factors. Significant differences were found in the preoperative LS (mean, 10.8° vs. 8.2°, p = 0.004), PO (median, 6.8° vs. 2.0°, p < 0.001), and HAA (median, 10.0° vs. 6.0°, p = 0.003). ΔLS was correlated with the preoperative LS (ρ =  − 0.621, p < 0.001), PO (ρ =  − 0.580, p < 0.001), and HAA (ρ =  − 0.467, p < 0.001). ΔPO was correlated with the preoperative LS (r =  − 0.596, p < 0.001), PO (ρ =  − 0.892, p < 0.001), and HAA (ρ =  − 0.728, p < 0.001). ΔHAA was correlated with the preoperative LS (r =  − 0.583, p < 0.001), PO (ρ =  − 0.751, p < 0.001), and HAA (ρ =  − 0.824, p < 0.001). LS, PO, and HAA were significantly improved after conversion THA. Greater improvement in LS, PO, and HAA can be expected in patients with larger preoperative LS, PO, and HAA values.